IMPLEMENTATION OF THE ACTIVITY BASED COSTING METHOD IN CONSTRUCTION - Diah Sarasanty; Erna Tri Asmorowati (LPPM Universitas Negeri Jakarta, 2023)
This study examines the factors that influence the application of the activity-based costing (ABC) method in construction projects. This research adopts a quantitative approach by developing a case study model. The study tested the model on a sample of 24 hydromechanical and gate works, weirs, irrigation networks, river protection, dams and ponds, coastal protection, swamp infrastructure, groundwater infrastructure, and raw water infrastructure. Primary data collected from field surveys. This study found that the proportion of indirect costs, competitive pressures in price and quality, and product diversification significantly influence a company's decision to apply the ABC method. There were found to be implications for managerial practice and public policy. It is hoped that this research will be useful in meeting the planning needs that are currently being addressed.